Full steam ahead: Insider knowledge, stock trading and the nationalization of the railways in Prussia around 1879 - Michael Buchner; Tobias A. Jopp (European Historical Economics Society (EHES), 2019)
The costs and benefits of insider trading is a persistent topic in the economic literature and public discourse alike. Nowadays insider trading is principally illegal and morally banned implying that the costs are supposed to weigh heavier than the potential benefits. We study insider trading pre-1914 in order to shed new light on its extent when it was still legal. Our focus is on the first wave of railway nationalisation in Prussia around 1879, the biggest financial transaction in German economic history by this time. Anecdotal evidence has it that insiders – e.g. involved banks or single bankers – made decent use of their exclusive knowledge on how nationalisation would proceed, thereby incurring huge profits. We show that insiders were active at the Berlin Stock Exchange, but contrary to anecdotal evidence could be so only in a very small time-window limiting their options sustainably. Contrary to what Braggion and Moore (2013) found for the London Stock Exchange, the rather modest extent of insider trading was not due to insiders' ethical reservations, but due to the stock exchange's institutional design that limited excessive insider trading in the absence of laws against it.
Keywords: D84; G14; N23; N73; 330; Abnormal Returns; Insider Trading; Nationalisation; Prussia; Railways